Performance of high-k dielectric material for short channel length MOSFET simulated using silvaco TCAD tools / Fatin Antasha Anizam ... [et al.] - Anizam, Fatin Antasha; Ismail, Lyly Nyl; Sihab, Norsabrina; Mohd Sauki, Nur Sa'adah (Universiti Teknologi MARA, 2021)
Short channel effect (SCE) occur in the MOSFET devices when the oxide layer became thinner, and the gate length become shorter. The purposed of this study is to find a new dielectric and gate material to replace the conventional oxide which is silicon dioxide (SiO2) and polysilicon as gate material. The objective of this study is to investigate the performance of MOSFET using different types of high-k dielectric material and germanium (Ge) as gate material. The MOSFET structure was fabricated and simulated using Silvaco TCAD tool. The overall performance of the MOSFET is evaluated based on the current-voltage (I-V) characteristics. Result show that MOSFET fabricated with HfO2 and Ge as dielectric and gate material has high drive current reduce leakage current by a factor of 0.55 from the conventional MOSFET. Therefore, combination of HfO2 and Ge in MOSFET structure has the best performance compared to SiO2 and poly silicon because it produces smaller leakage current and smaller Vth when shrinking the device sizes, hence reducing SCEs.